Penerapan Model Make a Match untuk Meningkatkan Pemahaman Peserta Didik materi Senang Bisa Membaca Q.S. Al-‘Asr di SDIT Darul Azzam - Taufik Hidayat; Syahrul Kamil (Kampus Akademik Publiser, 2024)
This study aims to improve students' understanding of the material Senang Bisa Membaca Q.S. Al-‘Asr through the application of the Make a Match cooperative learning model. The research subjects were 25 second-grade students at SDIT Darul Azzam in the 2024/2025 academic year. The method used was Classroom Action Research (CAR) with a Kemmis and McTaggart design consisting of planning, implementation, observation, and reflection stages. Data were obtained through observation of teacher and student activities, lesson plan assessment, and learning outcome tests. The results showed that in the pre-cycle, only 24% of students achieved mastery, while after cycle I, it increased to 48%, and in cycle II, 84% of students achieved mastery. Student activity also increased significantly from adequate to excellent. Thus, the application of the Make a Match model proved to create an active, enjoyable, and interactive learning atmosphere that had a positive impact on students' understanding of the material in Q.S. Al-'Asr.